PENGARUH PERGAULAN TEMAN SEBAYA TERHADAP PERILAKU SEKS PRANIKAH SISWA KELAS XI DI SMK YP 17 PARE KEDIRI - admin ilkes (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2017)
Adolescent has unique character, one of them character wants to imitate a certain matter that want to see fromenvironment. Social environment and negative culture be risk factor that can causes adolescent trapped in sex behavior before married. This plan research analyzes effect friend association coeval to sex behavior before married. This research method uses observasinal research kind with research design correlational and approach cross sectional. The independent variabel is effect friend association coeval and dependent variabel is sex behavior before married. The research was carried out on August 2017. The population numbers 100 respondents with sample size 80 respondents that fulfil criteria inklusi. Technique sampling used simple random sampling. Data was collecting uses questioner. Statistics test used chi-square.Based on 80 respondents got 66,2% respondent has friend association coeval negative and 22,5% respondent has attitude sex before married. Data was analysis uses chi-square got value result as 0,033 where 0,033 < 0,05. So that H0 aversed that mean there effect has significant between friend association coeval to sex behavior before married.Friend association coeval be important factor in sex behavior before married, because in adolescent, adolescent more rely on friend was compared the old person in gets information hits the sexual change. Sexual information from friend coeval can trip adolescent in sex behavior before married when did adolescent can’t filtered information from friend coeval well. Because of information got from friend coeval come from own self experience.